Pengaruh Gaya Kepemimpinan dan Motivasi terhadap Produktivas Kerja Karyawan Pada PT Berkat Cahaya Novena Jawa Barat - Veritia Veritia; Feb Amni Hayati; Lili Sularmi; Lily Setyawati Kristianti (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Employee productivity is a critical factor in achieving organizational goals, and it is strongly influenced by leadership style and motivation. In the dynamic work environment of PT Berkat Cahaya Novena, West Java, management effectiveness and employee motivation play a crucial role in determining performance outcomes. Observations and preliminary reports indicate that variations in leadership approaches and levels of employee motivation may lead to significant differences in productivity, making it necessary to examine these variables systematically. This study aims to investigate the effect of leadership style and motivation on employee productivity, both partially and simultaneously. The research employed a quantitative approach with an associative method. The population consisted of all 74 employees of PT Berkat Cahaya Novena, and a census sampling technique was applied. Data were collected using a structured questionnaire with closed-ended questions based on a 5-point Likert scale, distributed directly and via WhatsApp. The collected data were analyzed using SPSS 26 through multiple linear regression, including descriptive analysis, classical assumption tests, and regression analysis. The findings reveal that both leadership style and motivation have a significant positive impact on employee productivity. Strong leadership, characterized by guidance, support, and encouragement, enhances employee performance, while effective motivation further drives productivity by addressing employee needs and providing recognition. These results highlight the importance of implementing effective leadership practices and motivational strategies to optimize organizational performance.